Intergenerational justice: a useful perspective for heritage conservation - Joel Taylor (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This contribution discusses the emergent field of Intergenerational Justice (IJ) with an aim to drawing new light upon issues in conservation. Several key issues in IJ are discussed that allow heritage conservation to be contextualised. Methods and debates from IJ are described and related to conservation practice. The paper is not an exhaustive review, but identifies links to pertinent issues in conservation.